Analysis of Debt to Equity Ratio (DER) and Earning Per Share (EPS) on Stock Prices at PT Smartfren Telecom Tbk - Miftahul Jannah; Alwi (Pustaka Digital Indonesia, 2025)
This study investigates the impact of the Debt to Equity Ratio (DER) and Earnings Per Share (EPS) on the stock prices of PT Smartfren Telecom Tbk, a major telecommunication company in Indonesia. Employing a quantitative associative approach, the study utilizes secondary data from the company’s audited financial reports spanning 2012 to 2024. Multiple linear regression analysis is applied to determine the influence of DER and EPS on stock price movements. The results reveal that neither DER nor EPS has a statistically significant partial effect on stock prices. Moreover, the variables jointly exhibit no significant simultaneous impact. These findings suggest that investors may not rely solely on DER and EPS when evaluating investment opportunities in PT Smartfren Telecom Tbk. The study recommends future research to include additional financial indicators such as Debt to Asset Ratio, Net Profit Margin, and Price to Earnings Ratio to improve model explanatory power. Insights from this study contribute to a deeper understanding of how traditional financial ratios influence investor decision-making within Indonesia’s telecommunication sector.